2019
DOI: 10.26504/rs91.pdf
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effects on Irish hospital care of the supply of care inside and outside the hospital

Abstract: The mission of the Economic and Social Research Institute is to advance evidencebased policymaking that supports economic sustainability and social progress in Ireland. ESRI researchers apply the highest standards of academic excellence to challenges facing policymakers, focusing on 12 areas of critical importance to 21st Century Ireland.The Institute was founded in 1960 by a group of senior civil servants led by Dr T.K. Whitaker, who identified the need for independent and in-depth research analysis to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…An improved integration with post-acute hospital care could also reduce delayed discharges, allowing more hospital patients to be seen. Recent ESRI research has shown that hospital stays for older people are shorter in areas with better supply of home care and residential care services (Walsh et al, 2020b;Walsh et al, 2019). The flexibility of Hippocrates also allowed for analysis of the sensitivity of projected expenditures to assumed changes in public-sector pay policy.…”
Section: Policy Implications Reflections and Conclusionmentioning
confidence: 99%
“…An improved integration with post-acute hospital care could also reduce delayed discharges, allowing more hospital patients to be seen. Recent ESRI research has shown that hospital stays for older people are shorter in areas with better supply of home care and residential care services (Walsh et al, 2020b;Walsh et al, 2019). The flexibility of Hippocrates also allowed for analysis of the sensitivity of projected expenditures to assumed changes in public-sector pay policy.…”
Section: Policy Implications Reflections and Conclusionmentioning
confidence: 99%
“…First, there is a surprising lack of empirical analysis of the substitutability of acute and non-acute care and this needs to be addressed in order to inform policymakers tasked with implementing the goals set out in the current reform programme for Irish healthcare. Thus, this project seeks to contribute to the evidence base on the substitutability between acute and non-acute care (in Report 2 (Walsh et al, 2019b)). To further inform the debate on the transfer of care, there is need for information on what non-acute services are currently available, and how they are dispersed around the country, hence the focus of this report.…”
Section: Irish Healthcare Policy Contextmentioning
confidence: 99%
“…Acute care utilisation is a key part of the analyses in this project, so a more detailed description of acute public hospital services in Ireland is provided in the next report (Walsh et al, 2019b).…”
Section: Acute Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide context in which to frame a discussion of the healthcare system data infrastructure in Ireland, we provide a brief overview of the healthcare system itself. A number of recent ESRI publications discuss some of the specific parts of the system in greater detail (Keane et al, 2021;Nolan et al, 2014;Smith et al, 2019;Walsh et al, 2019a;Walsh et al, 2019b;Wren and Fitzpatrick, 2020;.…”
Section: Healthcare Systemmentioning
confidence: 99%